The analysis of the human condition in Arendt as a critique of an apolitical concept of freedom. A contemporary perspective - de Bruin Kloppers, Kai (Anales del Seminario de Historia de la Filosofía, 2023)
In this article I am going to show what, according to Arendt, would be an adequate notion of freedom. That is, a notion of freedom that is properly adapted to human possibilities and needs. Simultaneously, I will expose the inadequacy and the risks of attempting to achieve a form of freedom that is understood as something detached from the political realm, plurality and the public space. To do this, I will explore the links between the corruption of the human condition and, firstly, the transformation of the notions of labor and work after the industrial revolution, and, secondly, the displacement of the notion of freedom after the French revolution. Moreover, I will make a series of observations regarding the current state of our relationship with the world, as a human artifice, in the development of each one of the activities of our “vita activa”. These brief observations will have to do, on the one hand, with the changes that this relationship undergoes due to the acceleration of the pace of work and consumption resulting from the industrial revolution and, on the other hand, with the invasion of politics by the economy as a result of the French revolution.
Keywords: arendt; freedom; french revolution; industrial revolution; necessity; politics; work; world